Pengaruh Pengetahuan Zakat, Religiusitas Dan Motivasi Terhadap Minat Pembayaran Zakat Melalui Platform Digital Yang Bekerja Sama Dengan Baznas: (Studi Pada Generasi Milenial Di Kab. Jember) - Laelatul Putri Nur Azizah; Priyono, Teguh Hadi; Mahardiyanto, Agus (UPT Penerbitan Universitas Jember, 2025)
This research was conducted and completed to test and analyze the effect of zakat knowledge, religiosity, and motivation on the interest in paying zakat through digital platforms in collaboration with BAZNAS. This research is a quantitative study with questionnaire data collection techniques. The research subjects were millennial individuals domiciled in Jember Regency. This study used purposive sampling and obtained a sample of 101 respondents who met the predetermined criteria. The data analysis methods used include instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that partially, the variables of zakat knowledge, religiosity, and motivation have a positive and significant influence on the interest in paying zakat through digital platforms in cooperation with BAZNAS. Simultaneously, the three variables also have a significant effect on digital zakat payment interest. It can be concluded that millennials have high potential in supporting the digitalization of zakat when supported by adequate zakat knowledge, strong religious values, and internal as well as external motivation to participate in zakat payment. Therefore, zakat management institutions such as BAZNAS need to improve digital education and expand technology-based services to reach more zakat payers from the millennial generation.